The Association of Race, Socioeconomic Status, and Insurance on Trauma Mortality. Issue 6 (November 2016) - Mikhail, Judy N.; Nemeth, Lynne S.; Mueller, Martina; Pope, Charlene; NeSmith, Elizabeth G.; Wilson, Kenneth L.; McCann, Michael; Fakhry, Samir M.
Abstract : Background: Although race, socioeconomic status, and insurance individually are associated with trauma mortality, their complex interactions remain ill defined. Methods: This retrospective cross-sectional study from a single Level I center in a racially diverse community was linked by socioeconomic status, insurance, and race from 2000 to 2009 for trauma patients aged 18–64 years with an injury severity score more than 9. The outcome measure was inpatient mortality. Multiple logistic regression analyses were performed to investigate confounding variables known to predict trauma mortality. Results: A total of 4, 007 patients met inclusion criteria. Individually, race, socioeconomic status, and insurance were associated with increased mortality rate; however, in multivariate analysis, only insurance remained statistically significant and varied by insurance type with age. Odds of death were higher for Medicare (odds ratio [OR] = 3.63, p = .006) and other insurance (OR = 3.02, p = .007) than for Private Insurance. However, when grouped into ages 18–40 years versus 41–64 years, the insurance influences changed with Uninsured and Other insurance (driven by Tricare) predicting mortality in the younger age group, while Medicare remained predictive in the older age group. Conclusions: Insurance type, not race or socioeconomic status, is associated with trauma mortality and varies with age. Both Uninsured and Tricare insurance were associated with mortality in younger age trauma patients, whereas Medicare was associated with mortality in older age trauma patients. The lethality of the Tricare group warrants further investigation.